(untitled) (Research, Society and Development, 2020)
In view of the relevance of Mathematical Modeling in the area of Mathematical Education, we seek, based on articles from four periodicals with more than 25 years of existence and which were well evaluated by CAPES in teaching area, to outline an overview of publications on Mathematical Modeling, which covers the period of 1994 to 2019. The objective was to investigate what has been discussed, how it has been treated, what has been published about Mathematical Modeling and, with that, list aspects and point out characteristics of the publications that involve it. For this, searches were carried out on the websites of four journals that fit the criteria we established, thus obtaining ninety-two articles. Such articles were categorized according to the central themes that they deal with, on the criticality or not of the proposals they convey, according to the school levels in which proposals for Mathematical Modeling were developed and in relation to the contents that were addressed in these activities. The analyzes point out the main themes addressed over the past 26 years in these four journals, the predominance of critical perspective in the proposals for Mathematical Modeling, the preference for the development of Mathematical Modeling in high school and university education and the greater incidence of mathematical content related to functions. We believe that the discussions and suggestions presented in this article can enrich and direct new works that may involve Mathematical Modeling in Mathematical Education.